Jane Kelsey (2015) The FIRE Economy: New Zealand’s Reckoning. Wellington, New Zealand. Bridget Williams Books with the New Zealand Law Society. - Naoise McDonagh (International Journal for Crime, Justice and Social Democracy, 2017)
Not applicable